2011
DOI: 10.1016/j.molimm.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania mexicana promastigotes inhibit macrophage IL-12 production via TLR-4 dependent COX-2, iNOS and arginase-1 expression

Abstract: Highlights► TLR-4 activation by Leishmania mexicana promastigotes and CPB-deficient amastigotes. ► Prolonged, TLR-4 dependent iNOS and COX-2 expression by L. mexicana promastigotes. ► Enhanced TLR-4 dependent-arginase-1 expression. ► Regulation of IL-12 induction by an arginase-1 dependent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 49 publications
8
36
0
2
Order By: Relevance
“…As previously shown for macrophages infected with Leishmania mexicana (50), we also found that DC infection by L. amazonensis increases the phosphorylation of these three kinases. However, the increase of phosphorylation of JNK and p38 in infected cells was independent of A 2B receptor.…”
Section: Discussionsupporting
confidence: 90%
“…As previously shown for macrophages infected with Leishmania mexicana (50), we also found that DC infection by L. amazonensis increases the phosphorylation of these three kinases. However, the increase of phosphorylation of JNK and p38 in infected cells was independent of A 2B receptor.…”
Section: Discussionsupporting
confidence: 90%
“…COX-2 is the inducible isoform of COX pro-inflammatory enzyme [53] associated with the production of proteinoids under inflammatory conditions [64], such that it is expressed in only a few normal tissues and upregulated in inflamed tissues. A previous study showed that L. mexicana prolonged the induction of COX-2 in macrophages stimulated with LPS [59]. Thus, its expression was expected, although no differences were observed between lesions from Balb/c and C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 79%
“…Increasing evidence is indeed accumulating showing that the formation of ROS represents an essential pathway of TLR-dependent signaling in cells from immune and non-immune origin, which occurs mainly through the activation of various NOX isoforms (Tsung et al, 2007;Ogier-Denis et al, 2008;Gill et al, 2010). In addition, the pro-inflammatory signaling cascades triggered by TLR engagement enhance the expression of iNOS, and thus promotes the generation of NO (Lewis et al, 2011;Shweash et al, 2011). In turn, the concomitant generation of O 2 .-(by NOXs) and NO .…”
Section: Role Of Tlr Activation In the Generation Of Oxidantsmentioning
confidence: 99%